Characteristics of Bioethanol from Musa Salaccensis ZOLL - Dady Sulaiman; St Syahdan; Siti Maria Ulva (International Journal of Science and Society, 2021)
The high increase in energy use causes renewable energy solutions such as wind energy, geothermal energy, biomass and others. Biomass is one solution for Indonesia to obtain energy, because Indonesia has the potential for biomass, both biodiesel and bioethanol. The biomass to be studied is Bioethanol. Forest banana is a type of wild plant that grows in the forests of North Kalimantan and is not consumed by residents because there are many seeds in the banana. The purpose of this study was to examine the characteristics of bioethanol from forest bananas. The stages of the research method that will be carried out include several stages, namely 1) making bioethanol, 2) measuring ethanol content, and 3) testing the characteristics of bioethanol. The stages of bioethanol testing carried out characteristic tests including: 1) Ethanol Content Analysis, 2) Moisture Content Analysis, 3) Density Analysis, 4) Specific Gravity and API Gravity Analysis, 5) Calorific Value Analysis. Based on the research results obtained, the quality of the bioethanol produced has a density value and specific gravity in accordance with the bioethanol quality standard, which is 0.46. The calorific value which has a close relationship with API Gravity is close to the maximum value in the bioethanol quality standard, which is 3702.30 kcal/kg. The value of ethanol content and water content still does not meet the quality standards, namely 24.8% and 86%. This is due to the lack of distillation process in this study.